Analisis Indeks Kepuasan Pasien di Puskesmas Kedungmundu Kota Semarang - Tunjungsari, Irris Pramadanti; Sulandari, Susi; Fathurrochman, Fathurrochman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Puskesmas Kedungmundu Semarang has fungtions and tasks to give good health services to public. So, it could bring satisfaction of people. To follow up the statement above, in order to give services level. Besides, it can be an indicator for knowing what kind of service which need to be improved. It will be the supporter for services unit to improve its service quality.The aim of this research is to calculate pulic’s satisfaction index in scheme of improving health service at Puskesmas Kedungmundu Semarang. In the calculation of IKM for 14 items examined of services, each item has the same weightd value of 0,017. In order to simplify the interpretation of IKM, that is 25-100, so these result be conversed to 25 then be put into Cartesian diagram after being processed in order to have clearly result and also to understand the balance of performance of services and the public’s importance of service at Puskesmas Kedungmundu.These results show that the overall quality of basic health services at Puskesmas Kedungmundu Semarang has been good it can be seen from the IKM after conversion of 69,85 which was the interval from 62,51 to 81,25 conversion so the quality of service B and good service unit performance, but in the Cartesian diagram of the 14 elements of services in community satisfaction index still under performing elements, namely speed of service and convenience services,so it is still necessary to improve performance in that section.